2004
DOI: 10.1161/01.res.0000126501.34994.96
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Impairs the Insulin Signaling Pathway Promoting Production of Nitric Oxide by Inducing Phosphorylation of Insulin Receptor Substrate-1 on Ser 312 and Ser 616 in Human Umbilical Vein Endothelial Cells

Abstract: Abstract-It has been suggested that serine (Ser) phosphorylation of insulin receptor substrate-1 (IRS-1) decreases the ability of IRS-1 to be phosphorylated on tyrosine, thereby attenuating insulin signaling. There is evidence that angiotensin II (AII) may impair insulin signaling to the IRS-1/phosphatydilinositol 3-kinase (PI 3-kinase) pathway by enhancing Ser phosphorylation. Insulin stimulates NO production by a pathway involving IRS-1/PI3-kinase/Akt/endothelial NO synthase (eNOS). We addressed the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
164
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(178 citation statements)
references
References 33 publications
8
164
2
4
Order By: Relevance
“…Furthermore, okadaic acid, a serine/threonine phosphatase inhibitor, as well as phorbol ester, mimicked Ang II effects on PI 3-kinase and IRS-1 [36]. It has been recently shown that Ang II impairs the insulin signaling pathway towards the production of NO by inducing serine phosphorylation of IRS-1 on Ser 312 and Ser 616 , via JNK and ERK1-2 respectively, thus impairing the vasodilator effects of insulin mediated by the IRS-1/PI 3-kinase/Akt/eNOS pathway [42].…”
Section: The Early and Intermediary Events Affected By The Insulin Anmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, okadaic acid, a serine/threonine phosphatase inhibitor, as well as phorbol ester, mimicked Ang II effects on PI 3-kinase and IRS-1 [36]. It has been recently shown that Ang II impairs the insulin signaling pathway towards the production of NO by inducing serine phosphorylation of IRS-1 on Ser 312 and Ser 616 , via JNK and ERK1-2 respectively, thus impairing the vasodilator effects of insulin mediated by the IRS-1/PI 3-kinase/Akt/eNOS pathway [42].…”
Section: The Early and Intermediary Events Affected By The Insulin Anmentioning
confidence: 95%
“…Alternatively, Ang II may decrease IRS-1/PI 3-kinase association by rapidly inducing the tyrosine dephosphorylation of IRS-1 via the activation or up regulation of a protein-tyrosine phosphatase [42]. Results from this study suggest that Ang II and other agents that are able to induce serine phosphorylation of the IR, IRS-1, and/or PI 3-kinase, can contribute to insulin resistance in the blood vessels [42]. Thus, we believe that Ang II negatively modulates insulin signaling by stimulating multiple serine phosphorylation events in the early components of the insulin-signaling cascade.…”
Section: The Early and Intermediary Events Affected By The Insulin Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a utilização de inibidores de fosfatases de serina/treonina mimetizaram os efeitos da angiotensina II sobre IRS-1 e PI-3 quinase (30). Recentemente, foi demonstrado que a angiotensina II é capaz de bloquear os efeitos vasodilatadores da insulina através da fosforilação em serina do IRS-1 nos resíduos Ser 312 e Ser 616 , através da ativação das serina-quinase JNK e ERK1-2, o que leva à modulação negativa da via IRS-1/PI-3 quinase/Akt/ eNOS, diminuindo a produção de NO induzida por insulina (36 (38,40,43). Além disso, a SOCS-3 é capaz de ligar-se ao IRS-1/2, provocando sua degradação proteossômica, através de um mecanismo dependente de ubiquitinação (44) (figura 4).…”
Section: Sinalização Da Insulina E Aii E Doença Cardiovascular No Dmunclassified
“…O pré-tratamento destas células com angiotensina II leva à ativação da ERK 1/2 e da Jnk por um mecanismo molecular dependente da ativação do AT1. Estas serina-quinases, uma vez ativadas, promovem a fosforilação em serina do IRS-1, impedindo a ativação da eNOS mediada pela insulina (36). Portanto, nesse tecido, a angiotensina II é capaz de induzir resistência à insulina pela via do IRS-1 por um mecanismo dependente de Jnk e ERK 1/2.…”
Section: O Papel Da Map Quinase Na Interação Insulina X Angiotensinaunclassified